Pengaruh Iklan Media Sosial TikTok, Citra Destinasi, Online Customer Review di Google Maps Dan Harga Terhadap Minat Kunjung di Wisata Telogo Sewu Pandaan. - Zuhriyah, Lailatuz; Arifin, Rois; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study examines the influence of TikTok advertising, destination image, online customer reviews on Google Maps, and pricing on tourist visit intention to Telogo Sewu Pandaan. Using a quantitative explanatory approach, data were collected from 90 TikTok users familiar with the destination. Multiple linear regression analysis shows that all variables significantly influence visit intention, both simultaneously and partially. TikTok advertising and destination image emerged as dominant factors. These findings highlight the strategic role of social media and destination perception in attracting tourists. Keywords: TikTok Advertising, Destination Image, Online Customer Review, Price, Visit Intention, Telogo Sewu